Theory of C2Hx Species on Pt{110}(1 × 2): Structure, Stability, and Thermal Chemistry - ANGHEL, Alexandra T.; JENKINS, Stephen J.; WALES, David J.; KING, David A. (The journal of physical chemistry. B, 2006)
The adsorption of C2Hx (x=0-5) hydrocarbon fragments on Pt{110}(1x2) has been investigated using calculations based on density functional theory. For all the species, the most stable adsorption site identified completes the tetravalency of each carbon atom and involves the maximum possible number of Pt atoms subject to that constraint. The most stable adsorption sites for C2Hx fragments of stoichiometry x=2-5 involve ridge atoms, while trough sites stabilize C2H and C2 species. The relative stability of the fragments involved is compared via a free energy picture.